Lead in Kuala Lumpur Urban Dust - Lee, C. K.; Low, K. S.; Lim, C. G (1988)
A preliminary survey of lead in Kuala Lumpur urban dust was carried out. Lead levels of22.9 to 6986.6 JJgg-l were obtained, depending on the locations where.the dust was collected. There is a direct relationship between lead level in dust and traffic density. The amount of lead leachable by rain water is sufficiently high to warrant further investigation.